Defining the measures to rationally manage the sustainable development of agricultural land use - Gorlachuk, Valery; Lazarieva, Olena; Belinska, Svitlana; Potapsky, Yuri; Petryshche, Olha (Eastern-European Journal of Enterprise Technologies, 2018)
The issue of socio-economic development of rural areas was explored. It was substantiated that the state policy should be aimed at mobilizing labor, financial, material and organizational resources, strengthening the social security of rural population, rehabilitation of social infrastructure, development of entrepreneurship, and maintaining ecological stability. It was proved that within the integrated management of the development of rural areas, the development of the system of local self-government in rural territory communities requires special attention. The factors that led to an unprecedented socio-economic and ecological crisis in agricultural land use were explored. Based on the solution of the optimization problem, the negative trends in the dynamics of key indicators of agricultural production, determined especially clearly on the basis of the results of the correlation data analysis. The obtained mathematical model of the dynamics makes it possible to foresee the consequences of unsustainable management of the development and even to predict the sad ending, unless certain priority factors of management are accepted. The prediction based on such a mathematical model of dynamics can be made by any indicators of agricultural production. It was noted that the modern period of development of land relations in rural areas will be able to satisfy the interests of the peasants only on condition of harmonious combination of economy of different spheres of activity in rural areas, which are reinforced one after another. The innovative approach to ensuring deficit-free balance of humus in soil as a condition for the sustainable development of agricultural land use was substantiated. It was determined that the policy, aimed at the environmental land use stabilization is based on the development of organizational-legal forms of economy of a cooperative type, based on the common share ownership of land plots of land share owners.